Simple and rapid nicotine analysis using a disposable silica nanochannel-assisted electrochemiluminescence sensor. Issue 14 (26th June 2020) - Xiao, Yi; Chen, Suhua; Zhang, Guocan; Li, Zhimao; Xiao, Han; Chen, Chuanpin; He, Chunlian; Zhang, Ran; Yang, Xiaoping
Abstract : A simple, rapid and disposable electrochemiluminescence sensor was developed for on-site nicotine analysis. Abstract : Nicotine analysis is essential to medicine, toxicology and the tobacco industry. However, no simple, portable and disposable method was developed to meet their demands. Here, we report a simple, rapid and disposable silica nanochannel (SAN)-based electrochemiluminescence (ECL) sensor for nicotine analysis by simply assembling a SAN electrode with a paper cover. The sensing principle of the disposable sensor is based on the size exclusion effect and charge selectivity, which obviously prolong the sensor service time. We find that the sensor exhibits good specificity to nicotine, and most of the complex matrices are unlikely to impact the detection. The performance of the disposable sensor in cigarettes, e-cigarettes, nicotine gums, and lozenges is fully validated, showing satisfactory linearity, sensitivity (a limit of detection of 27.82 nM), and accuracy (a recovery between 96.00% and 106.51%). The disposable sensor can be potentially applied for on-site nicotine analysis.